Sustainable Solution to Antibiotic Resistance: Pavetta indica-Based Nanomedicine - Baskaran, Thanaraj; Koperuncholan, Marimuthu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The escalating global health crisis, characterized by the emergence of antimicrobial-resistant pathogens, necessitates innovative strategies. This study explores the potential of Pavetta indica, a previously underutilized plant, as a multifaceted resource for addressing this critical challenge. A comprehensive phytochemical investigation unveiled a rich repertoire of bioactive compounds within P. indica, including essential metabolites Moisture (9.14%), Crude Protein (10.93%), and Crude Fiber (15.46%). Additionally, significant levels of Calcium, Phosphorus, and Ether Extract were identified, suggesting its potential contribution to a balanced diet and a diverse array of secondary metabolites identified through GC-MS analysis identified diverse bioactive compounds including Dodecanoic acid, Lupeol, and β-D-Glucopyranose among others, highlighting its potential health benefits and paving the way for further research on specific bioactivities. P. indica extract exhibited concentration-dependent ABTS and DPPH scavenging activities, comparable to ascorbic acid. This underscores its potential as a natural antioxidant source to combat oxidative stress-related diseases. Leveraging the bio-reducing capabilities of P. indica extract, we embarked on the green synthesis of silver nanoparticles. P. indica extract successfully synthesized silver nanoparticles, confirmed by UV-Vis spectroscopy (SPR band at 420 nm) and TEM (spherical particles, 25-50 nm). These nanoparticles showed potent antimicrobial activity against Bacillus subtilis, E. coli, and Pseudomonas aeruginosa, comparable to Gentamicin. The synthesized silver nanoparticles demonstrated concentration-dependent antifungal activity against Candida albicans, Aspergillus fumigatus, and Sporothrix schenckii, suggesting their potential as effective antifungal agents. Our findings underscore the significance of exploring underutilized plant resources for developing innovative solutions to pressing global health challenges. By integrating phytochemistry, nanotechnology, and microbiology, this research offers a promising approach to combating antimicrobial resistance. The study's outcomes lay the groundwork for future investigations into the underlying mechanisms of antimicrobial action, optimization of nanoparticle properties, and preclinical evaluation of their therapeutic efficacy.